Local level health preparedness for adverse weather: A review of Community Risk Registers in England - Agnes Jung; Richard Kopnyicky; Katya Brooks; Emily Loud; Sharif Ismail; Agostinho Moreira de Sousa; Daniel Blake (The Journal of Climate Change and Health)
Background: The increasing frequency of adverse weather events due to climate change poses challenges for emergency planning, response and recovery. While many countries have national plans for preparedness and response to specific hazards, the extent to which these plans influence local health risk management strategies is unclear. Methods: An assessment of Community Risk Registers (CRRs) published by Local Resilience Forums (LRFs) in England was conducted in 2023. The assessment criteria applied spanned recognition of disaggregated adverse weather risks, through to incorporation of guidance from national agencies within the CRRs. Results: Of the 33 (out of 38) CRRs reviewed, only half referenced adverse weather risks, and around half referenced relevant national and local guidance to support preparedness and response to minimise potential health impacts. Only two CRRs met all assessment criteria (i.e., the referencing of adverse weather risks, as well as national, local and UK Health Security Agency (UKHSA) specific public health guidance on adverse weather risks). Conclusions: There is a need to support strengthened inclusion of national evidence and guidance into local risk assessments and the translation of these into relevant documents to raise public awareness of the health impacts from adverse weather.